Micro-drill online sorting system - ZHAO RUJIE; ZHANG LONG; LV JIANGWEN; TANG XIAOHONG; LIU CHENGQI; XIONG GUOLIANG; LIU YANGYUAN (2022)
The invention relates to the technical field of online detection, and discloses a micro drill online sorting system which comprises an assembly line, a follow fixture, a feeding mechanism, a clamping mechanism, a detection mechanism and a sorting mechanism. A limiting mechanism and a locking mechanism are arranged on the assembly line; the feeding mechanism is responsible for conveying tidily arranged micro drills to the clamping mechanism, the clamping mechanism is responsible for placing the micro drills on the limited follow fixtures located on the assembly line, the detection mechanism is responsible for detecting the follow fixtures and the micro drills on the follow fixtures, and the detected follow fixtures and the detected micro drills are classified through the sorting mechanism; detection and sorting of the semi-finished micro-drills are automatically modified, all the semi-finished micro-drills can be detected online in real time and sorted according to the detection result, then the micro-drills w